2003
DOI: 10.1354/vp.40-4-376
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Clostridium perfringens β2-Toxin in the Gastrointestinal Tract of Horses

Abstract: Abstract. Clostridia-associated intestinal disease in horses was generally reported to be due to infection with Clostridium perfringens type A, which harbors the cpa-encoded ␣-toxin. A recent study demonstrated a high incidence of ␤2-toxigenic C. perfringens in horses suffering or dying from typhlocolitis, suggesting that this novel type of C. perfringens might play an important role in typhlocolitis and possibly other equine intestinal diseases. A retrospective study was conducted to assess the presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 26 publications
4
43
0
Order By: Relevance
“…Recently, the newly discovered beta 2 toxin has been associated with porcine, equine and bovine gastro-enteritis Bacciarini et al, 2003;Waters et al, 2003). This toxin has also been demonstrated in avian C. perfringens type A strains , but its exact role in pathogenesis needs to be further elucidated.…”
Section: Perfringens Virulence Factorsmentioning
confidence: 99%
“…Recently, the newly discovered beta 2 toxin has been associated with porcine, equine and bovine gastro-enteritis Bacciarini et al, 2003;Waters et al, 2003). This toxin has also been demonstrated in avian C. perfringens type A strains , but its exact role in pathogenesis needs to be further elucidated.…”
Section: Perfringens Virulence Factorsmentioning
confidence: 99%
“…Beta2 toxin, encoded by cpb2, which is another toxin produced by many C. perfringens isolates (Gibert et al, 1997), has been associated with NE in horses (Bacciarini et al, 2003), ruminants (Lebrun et al, 2007), and pigs Waters et al, 2003). However, it has been suggested that beta2 toxin is not involved in NE in poultry (Gholamiandekhordi et al, 2006;Crespo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Clostridium perfringens β-toxin is known to be the primary pathogenic factor of necrotic enteritis in type C strains that produce β-toxin. Necrotizing enteritis is believed to be due to the production of β-toxin by Clostridium perfringens type C. Clostridium perfringens β-toxin can also cause dermonecrosis and oedema in the dorsal skin of animals [16][17][18] . This paper describes the successful isolation and cloning of α-toxin and β-toxin genes from the strains NCTC64609 and C58-1 of Clostridium perfringens respectively.…”
Section: Discussionmentioning
confidence: 99%